Thrombocytopenia in a cohort of primary and secondary antiphospholipid syndrome patients: Relation to clinical, laboratory manifestations and damage index - Sherif Gamal; Samar Mohamed; Abdelkawy Moghazy (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate the prevalence of thrombocytopenia in a cohort of patients with primary and secondary antiphospholipid syndrome (APS) and to examine the relation of thrombocytopenia to the clinical, laboratory findings, and damage index for antiphospholipid syndrome (DIAPS). Patients and methods: Between August 2018 and February 2019, a total of 168 patients (16 males, 152 females; mean age: 32.5±8.4 years; range, 18 to 59 years) who were followed in our clinic for APS were retrospectively analyzed. Medical records of the patients were screened and clinical data, laboratory investigations, and treatments applied were recorded. The DIAPS was calculated for all patients. The patients were divided into two groups according to the presence or absence of thrombocytopenia and both groups were compared regarding clinical, laboratory findings and DIAPS. Further subgroup analysis was done for patients with primary APS. Results: The most common clinical manifestations in our patients were obstetric manifestations (77.4% in pregnant women), musculoskeletal manifestations (69%) and peripheral vascular thrombosis (54.8%). The prevalence of thrombocytopenia in our study was 42.3%, and it was significantly associated with musculoskeletal manifestations (p=0.043), vascular thrombosis (p=0.043), neurological manifestations (p=0.030), cutaneous manifestations (p=0.006), and use of immunosuppressives (p=0.047). The DIAPS was significantly higher in the thrombocytopenia group (p=0.034). Further subgroup analysis of patients with primary APS revealed that neurological manifestations (p=0.010) were significantly higher in the thrombocytopenia group, while the DIAPS was higher in the thrombocytopenia group, but it did not reach statistical significance (p=0.082). Conclusion: Thrombocytopenia may be associated with a higher incidence of vascular thrombosis, neurological manifestations, musculoskeletal manifestations, use of immunosuppressive treatment, and DIAPS. In primary APS patients, thrombocytopenia may be a risk for neurological manifestations.